1998
DOI: 10.1093/treephys/18.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Thigmomorphogenesis: a dose response to flexing in Ulmus americana seedlings

Abstract: Six-week-old half-sib seedlings of Ulmus americana L. were subjected to different amounts of flexure daily for 3 weeks under controlled greenhouse conditions. The daily flexure treatments were: no flexing in a staked stem, minimal flexing in a non-staked stem, and five, 10, 20, 40, and 80 flexures. Seedling height and diameter growth and average leaf area were determined before and after the treatments. The ratio of the change in height growth (DeltaH) to the change in diameter growth (DeltaD; (DeltaH:DeltaD))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
1
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 8 publications
7
82
1
1
Order By: Relevance
“…While our results showed that T tilting does not affect growth and R/S ratios significantly, wind or other mechanical perturbations such as flexing had a direct effect of increasing radial growth, reducing stem elongation, and decreasing total biomass above ground (Telewski and Jaffe 1986;Stokes et al 1997;Telewski and Pruyn 1998;Kern et al 2005). Significant clonal differences were seen in the R/S ratio (Table 3).…”
Section: Growth and Biomasscontrasting
confidence: 55%
“…While our results showed that T tilting does not affect growth and R/S ratios significantly, wind or other mechanical perturbations such as flexing had a direct effect of increasing radial growth, reducing stem elongation, and decreasing total biomass above ground (Telewski and Jaffe 1986;Stokes et al 1997;Telewski and Pruyn 1998;Kern et al 2005). Significant clonal differences were seen in the R/S ratio (Table 3).…”
Section: Growth and Biomasscontrasting
confidence: 55%
“…In the month prior to planting, the accumulated rainfall was 230 mm, and during the evaluation period the cumulative value was 502 mm, with an air temperature of 20.8 ± 1.1 °C and relative humidity of 68.8 ± 3.7%. However, during the same period wind speed peaked between 62.6 to 85 km h which are capable of altering plant growth (TELEWSKI, 2012). Thus, under those conditions, the mechanical stimulus applied in the nursery triggered mechanisms of tolerance to external stimuli, resulting in greater success in establishing P. taeda seedlings, as growth at ninety days after planting were strongly influenced by the frequency of swayings applied in the nursery and the wind velocity was on the average higher than that recommended by Telewski (2012).…”
Section: Discussionmentioning
confidence: 99%
“…Response of plant growth to mechanical disturbance was coined as thigmomorphogenesis by Jaffe (1973) which causes reduction of primary growth (TELEWSKI; PRUYN, 1998;COUTAND et al, 2010), changes biomechanical properties of wood (CORDERO, 1999) and stimulates biosynthesis and chemical composition of lignin (KERN et al, 2005;HAMANN et al, 2009;SAIDI et al, 2011;RAMOS et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In trees, mechanical stimulation of the stems will increase their elasticity, requiring a larger cross section to maintain stiffness [21,88]. Trees will also slow height growth when exposed to wind [88,89]. Lundqvist and Elfin [90] worked with a Scot's pine (Pinus sylvestris L.) plantation where the trees had been planted using a repeated pattern of various spacings, thus creating a range of repeated spacings within the stand.…”
Section: Resultsmentioning
confidence: 99%